ZnO Nanostructures for Tissue Regeneration, Drug-Delivery and Theranostics Applications - Cauda, Valentina; Laurenti, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nanostructured zinc oxide materials are capturing a great deal of interest thanks to their outstanding and multifunctional properties, enabling broad series of intervention in the field of nanomedicine. ZnO can be easily prepared in a broad variety of shapes and shows anticancer and antimicrobial properties that are of interest for tissue engineering, controlled delivery of therapeutics, and even theranostics. This book is thus dedicated to the most recent advances in the field, presented as a collection of research papers and reviews. It spans from the synthesis and characterization of ZnO nanomaterials to their applications in the nanomedicine field, ranging from anticancer nanotherapeutics to dental implants and antibacterial agents.